Interactivity and Interpersonality Elements Produced by College Students in Spoken Discourse - Rokhayani, Atik; Wijayanti, Dina Novita; Tardaguila, Pauline Joy Gelacio; Shofiyuddin, Muh (Journal of English Teaching and Learning Issues, 2024)
Speaking tends to be a difficult skill for Indonesian students. To overcome the problem, one can use discourse markers (interactivity and interpersonality elements) for a conversation.  The purposes of the study are to explain the kinds of interactivity and interpersonality elements and the implementation of interactivity and interpersonality elements of spoken discourse produced by college students. The study belongs to qualitative research. The data are the elements of interactivity and interpersonality, while the data source is transcripts of job interviews. The instrument of this study is documentation. Based on the findings, all interactivity and interpersonality elements are found in the data source. Based on the findings of the study, all kinds of interactivity and interpersonality elements are found in the data source. The students dominantly use discourse markers as first rank to fill the gap between previous and next utterances and maintain the stability of the conversation. In contrast, their application in the spoken discourse of college students is still low because only one element out of four is used dominantly (more than 50%). In order to address the issue, students must enhance their self-confidence in speaking English. Also, consistent practice leads to improvement.